World energy supplies / 1963-1966. - United Nations; United Nations (New York : Statistical Office of the United Nations, 1968)
National Oil Companies (NOCs) play an important role in the world economy. They produce most of the world's oil and bankroll governments across the globe. Although NOCs superficially resemble private-sector companies, they often behave in very different ways. Oil and Governance explains the variation in performance and strategy for NOCs and provides fresh insights into the future of the oil industry as well as the politics of the oil-rich countries where NOCs dominate. It comprises fifteen case studies, each following a common research design, of NOCs based in the Middle East, Africa, Asia, Latin America and Europe. The book also includes cross-cutting pieces on the industrial structure of the oil industry and the politics and administration of NOCs. This book is the largest and most systematic analysis of NOCs to date and is suitable for audiences from industry and academia, as well as policy makers".
Issues carry also United Nations publication sales numbers.
aia 26/02/2019
Loans
Keywords: Energy industries; Power resources; Energy industries